RECENT PROGRESS OF DENDRIMERS IN DRUG DELIVERY FOR CANCER THERAPY - Anitha, P.; Bhargavi, J.; Sravani, G.; Aruna, B.; S., Ramkanth (International Journal of Applied Pharmaceutics, 2018)
With the recent advances of nanotechnology, dendrimers are emerging as a highly attractive class of drug delivery vectors for cancer therapy. Dendrimers are multifunctional smart Nanocarriers to deliver one or more therapeutic agent safely and selectively to cancer cells. The high level of control over the synthesis of dendritic architecture makes dendrimers a nearly perfect (spherical) nanocarrier for site-specific drug delivery. The presence of functional groups in the dendrimers exterior also permits the addition of other moieties that can actively target certain diseases which are now widely used as tumor targeting strategies. Drug encapsulation, solubilization and passive targeting also equally contribute to the therapeutic use of dendrimers. Dendrimers are ideal carrier vehicles on cytotoxicity, blood plasma retention time, biodistribution and tumor uptake. In this review we highlight the advantages of dendrimers over conventional chemotherapy, toxicity and its management, following anti-cancer drugs delivered by using dendrimers and recent advances in drug delivery by various types of dendrimers as well as its diagnostic applications.